Soluble TIM3 and Its Ligands Galectin-9 and CEACAM1 Are in Disequilibrium During Alcohol-Related Liver Disease and Promote Impairment of Anti-bacterial Immunity - Riva, Antonio; Palma, Elena; Devshi, Dhruti; Corrigall, Douglas; Adams, Huyen; Heaton, Nigel; Menon, Krishna; Preziosi, Melissa; Zamalloa, Ane; Miquel, Rosa; Ryan, Jennifer M.; Wright, Gavin; et al. (Frontiers in Physiology, 2021)
Immunoregulatory checkpoint receptors (CR) contribute to the profound immunoparesis observed in Alcohol-related liver disease (ALD) and in vitro neutralisation of inhibitory-CRs TIM3/PD1 on antibacterial T-cells can rescue innate and adaptive antibacterial immunity. Recently described soluble-CR forms can modulate immunity in inflammatory conditions, but the contributions of soluble-TIM3 and soluble-PD1 and other soluble-CRs to immune derangements in ALD remain unclear. In Alcoholic Hepatitis (AH; n=19), alcohol-related cirrhosis (ARC; n=53) and healthy control (HC; n=27) subjects, we measured by luminex technology (i) plasma levels of 16 soluble-CRs, 12 pro-anti-inflammatory cytokines and markers of gut bacterial translocation (ii) pre-hepatic, post-hepatic and non-hepatic soluble-CR plasma levels in ARC patients undergoing TIPS; (iii) soluble-CRs production from ethanol-treated immunocompetent precision cut human liver slices (PCLS); (iv) whole-blood soluble-CR expression upon bacterial challenge. By FACS, we assessed the relationship between soluble-TIM3 and membrane-TIM3 and rescue of immunity in bacterial-challenged PBMCs. Soluble-TIM3 was the dominant plasma soluble-CR in ALD vs HC (p=0.00002) and multivariate analysis identified it as the main driver of differences between groups. Soluble-CRs were strongly correlated with pro-inflammatory cytokines, gut bacterial translocation markers and clinical indices of disease severity. Ethanol exposure or bacterial challenge did not induce soluble-TIM3 production from PCLS nor from whole-blood. Bacterial challenge prompted membrane-TIM3 hyperexpression on PBMC from ALD patient’s vs HC (p<0.002) and was inversely correlated with plasma soluble-TIM3 levels in matched patients. TIM3 ligands: soluble-galectin-9 and soluble-CEACAM1 were elevated in ALD plasma (AH>ARC; p<0.002). In-vitro neutralisation of Galectin-9 and soluble-CEACAM1 improved the defective antibacterial and anti-inflammatory cytokine production from E-coli-challenged PBMC in ALD patients. ALD patients exhibit supra-physiological plasma levels of soluble-TIM3, particularly in those with greater disease severity, this is also associated with increased levels of soluble TIM3-ligands and membrane-TIM3 expression on immune cells. Soluble-TIM3 can block the TIM3-ligand synapse and improve anti-bacterial immunity; however, the increased levels of soluble TIM3-binding ligands in patients with ALD negate any potential immunostimulatory effects. We believe that anti-TIM3 neutralising antibodies in Phase-I clinical-trials or soluble-TIM3 should be investigated further for their ability to enhance antibacterial immunity. These agents could represent an innovative immune-based approach to rescue antibacterial defences in ALD patients.